Political Network Patterns Of Village Head Dynasty In Red Mata Village, Banyuasin I District Banyuasin District - Marzuki, M. Ervan; Munandar, Aris (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2024)
The dynastic political network pattern is a series of human politics for acquire power but it is on his side by inheritance power that has been held over other people who have ties of power with previous power holders. Based on this, the study This research aims to determine the pattern of political network formation dynasty and the impact it had on the political behavior of the village community Red Eyes, Banyuasin I District, Banyuasin Regency. This research uses qualitative methods to describe and explains the pattern of formation of dynastic political networks and their impacts impact on political behavior. Data collection techniques used includes observations, interviews and documentaries. The research results show that the political network pattern of the head dynasty villages in Merah Mata Village, Banyuasin I District, Banyuasin Regency include 1) Capital Economy: The Red Mata Village Chief has stable economic capital, however has a familial relationship with the previous village head so belonging to dynastic politics, 2) Cultural Capital: Character and competence The Red Eye Village Head is much more important because it has an impact on the process decision making and benchmarks for action, 3) Social Capital: Head Merah Mata Village has good social capital, which can be seen in its role in creating and participating in community activities, and 4) Capital Symbolic: The Head of Merah Mata Village has classified symbolic capital lacking, but he was able to improve the welfare of his people. As for the impact arising from the political dynasty in Merah Mata Village, namely restrictions opportunities for other people who are more worthy to occupy positions as Head of Red Eye Village.